Financial Analysis of Broiler Chicken Farmers on Partnership Pattern and Independent Pattern - V A Siallagan; I Sembiring; S Sepriadi; D Purba; R E Mirwandhono (Talenta Publisher, 2020)
Broiler farm business continues to grow. This research aims to find out the income and feasibility reviewed from financial aspect of broiler chicken farmers partnership patterns and independent patterns in Tanjung Morawa Sub-district. The type of data used in this study is primary data obtained through observation and interviews and secondary data. Determination of samples with purposive sampling with broiler chicken breeders partnership pattern as many as 9 people and broiler chicken farmer independent pattern as many as 3 people. Data analysis was observed by calculating revenue income and financial viability of Revenue Cost Ratio, Break Event Point, Return on Investman and Internal Rate of Return. The results showed that the average income per head breeder of partnership patterns with company A, company B and company C amounted to Rp 2,216, Rp2,407, Rp 2,310 and the average income of independent pattern farmers amounted to Rp 3,077. Broiler business farmers partnership obtained ROI of 63%-80%, IRR is greater than the interest rate, which is 22%-24% and R/C more than one. Based on the feasibility criteria of financial analysis of partner and independent pattern farms is feasible to run and develop.